EFEKTIVITAS METODE PERKULIAHAN DI PRODI PGSD UNIVERSISTAS ABDURACHMAN SALEH SITUBONDO - Aenor Rofek (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2017)
The effectiveness of teaching and learning can be determined by the method used by the lecturer. Often the lessons practiced in the teaching and learning process stagnate, even the students feel bored to learn. Not because the lesson is boring or feared, but the saturation of students arises from the methods used by lecturers. One of them is monotonous teaching, where lecturers as educators are only limited to deliver without any self-evaluation and correction to the method of learning. Effective learning methods, especially in Teachers 'profession course, will affect the students' self-reliance in learning. However, these effective methods are not fully accomplished, even in many teaching and learning processes, especially in the field of the Teacher profession seem less effective. The Factors that can make effective lessons depend on the lecturers in using learning strategies and able to provide enthusiasm for students. effective learning in improving students' understanding of semester V in Prodi PGSD Abdurachman Saleh University conducted with the practice of reading every time the meeting. Such ways according to the lecturer of Teacher Training Profession at PGSD Prodi University Abdurachman Saleh is part of effective learning method in improving the defense in teacher profession course for students. The method undertaken by lecturers profession profession in Teachers PGSD University Abdurachman Saleh in improving the understanding of students by using various methods involving students in learning activities, namely the use of demonstration methods, Jigsaw and group discussion as the main method in the effectiveness of learning while those who do not effectively covering lecture method, and Snow Ball Trowing